The 'Alids - Teresa Bernheimer (Edinburgh University Press, 2013)
The respect and veneration accorded to the family of the Prophet Muá¸¥ammad are unparalleled in Islamic society. Political or religious affiliations notwithstanding, the Prophetâ€™s family â€“ most importantly his descendants through his daughter FÃt.ima and his cousin ÃAlÃ b. AbÃ Ã“Ãlib, collectively known as the ÃAlids â€“ were held in high esteem even by those who rejected their claims to the leadership of the Muslim community. Within the hierarchy of Islamic society, the ÃAlids were â€˜a blood aristocracy without peerâ€™.1 Although they clearly occupied a privileged place among Muslims from the earliest period of Islam, the social prominence of the Prophetâ€™s kin was by no means a foregone conclusion. In political as well as religious terms, those who became the heirs and successors to the Prophet in the majority of Muslim communities were generally not his descendants: Political authority came to be exercised by the caliphs while religious leadership went to the scholars. Yet, despite their virtual exclusion from the leadership of the Muslim communities, both politically and religiously, the ÃAlids nevertheless became the one indisputable nobility of Islam. This book provides the first social history of the ÃAlids in the crucial five centuries from the ÃAbbÃsid Revolution to the SaljÃ™qs (second/eighth to sixth/twelfth centuries). This period saw the formulation of many aspects still associated with the special position of sayyids and sharÃfs in Muslim societies, from their exemption from some of the rules that governed ordinary Muslims to the development of â€˜ÃAlidismâ€™. In contrast to ShiÊ¿ism, defined as the political and religious claims made by some members of the Prophetâ€™s family or by others on their behalf, ÃAlidism is characterised by a distinctly cross-sectarian reverence and support for the Prophetâ€™s family. As even a staunch Sunni like Ibn Taymiyya (d. 728/1328) notes: â€˜There is no doubt that MuÃŽammadâ€™s family (Ãl MuÃŽammad ) has a right on the Muslim society (umma) that no other people share and that they are entitled to an added love and affection to which no other branches of Quraysh are entitled.â€™2